2020
DOI: 10.1175/jtech-d-19-0105.1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Instrument Rainfall-Rate Estimation in the Peruvian Central Andes

Abstract: Agriculture is one of the main economic activities in the Peruvian Andes, rain water alone irrigates more than 80% of the fields used for agriculture purposes. However, the cloud and rain generation mechanisms in the Andes still remain mostly unknown. In early 2014, the Instituto Geofísico del Perú (IGP) decided to intensify studies in the central Andes to better understand cloud microphysics; the Atmospheric Microphysics And Radiation Laboratory officially started operations in 2015 at IGP’ Huancayo Observato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The main characteristics of all radars can be observed in Table 1. More information about inter-comparison between BLTR, CLAIRE and MIRA-35C can be found in [19].…”
Section: Radars and Sensorsmentioning
confidence: 99%
“…The main characteristics of all radars can be observed in Table 1. More information about inter-comparison between BLTR, CLAIRE and MIRA-35C can be found in [19].…”
Section: Radars and Sensorsmentioning
confidence: 99%
“…The DSD data output from the WS100 sensors consists of a table with the number of (e.g., [9,14,15]).…”
Section: Drop Size Distribution (Dsd)mentioning
confidence: 99%
“…Further comparisons of the Parsivel 2 with 2D-video disdrometers have shown that the Pasivel 2 underestimates drops smaller than 0.76 mm and overestimates drops greater than 4 mm [12], and corrections have been proposed to improve data quality [6,7]. Valdivia et al [9] compared the Parsivel 2 with tipping bucket rain gauges and a couple of radar profilers in the central Andes (3315 m MSL), founding a systematic underestimation in the event rain totals (18% bias and 19% absolute bias). However the Parsivel 2 measurements are even more reliable than those provided by radar, and DSD retrievals are necessary for the radar algorithms optimization [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the Lufft is a brand of OTT Hydromet (www.ott.com, accessed on 4 February 2022) and has been developing and producing professional components for climate and environment for more than 135 years. Some OTT instruments such as the optical disdrometer Parsivel 2 have been extensively used and evaluated (e.g., [5][6][7][8][9][10]). However, the WS100 rain sensor practically unknown in the scientific world and there are no studies evaluating how reliable its DSD retrievals are, as it is the case with the Parsivel 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Further comparisons of the Parsivel 2 with 2D-video disdrometers have shown that the Pasivel 2 underestimates drops smaller than 0.76 mm and overestimates drops greater than 4 mm [13], and corrections have been proposed to improve data quality [6,7]. Valdivia et al [9] compared the Parsivel 2 with tipping bucket rain gauges and a couple of radar profilers in the central Andes (3315 m MSL), founding a systematic underestimation in the event rain totals (18% bias and 19% absolute bias). However the Parsivel 2 measurements are even more reliable than those provided by radar, and DSD retrievals are necessary for the radar algorithms optimization [14].…”
Section: Introductionmentioning
confidence: 99%